Chronicity of infection with Treponema paraluis-cuniculi in New Zealand white rabbits. - DiGiacomo, R F (1985)
Popliteal lymph nodes from eight New Zealand white rabbits with clinical or serological evidence of naturally acquired infection with Treponema paraluis-cuniculi were transferred to rabbits that had not been exposed to this infection. Lymph nodes from two rabbits successfully transmitted infection. The nodes from one of these rabbits transmitted infection during both the acute and chronic stages of infection. Recipients that were successfully infected showed concomitant antibody responses in the Venereal Disease Research Laboratory (VDRL), rapid plasma reagin (RPR), and fluorescent treponemal antibody-absorption (FTA-ABS) tests six to 10 weeks after inoculation; recipients of uninfected nodes showed no change in serological state. Antibody responses were followed by the development of dark field positive genital lesions 14 to 15 weeks after inoculation.